2011
DOI: 10.2478/v10181-011-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent changes of cytokines mRNA in bronchoalveolar lavage fluid from symptomatic Recurrent Airway Obstruction-affected horses

Abstract: During an 18 day test, we measured the cytokine mRNA expression (Interleukin-1β , , Interferon-γ [IFN-γ], Tumor Necrosis Factor-α [TNF-α]) of cells from bronchoalveolar lavage fluid [BALF] in five horses previously diagnosed with RAO, before and during challenge exposure, and after the desensitization phase which involved dexamethasone treatment and environmental modification. Simultaneously, the same cytokine mRNA expression of cells from BALF in four asymptomatic RAO-affected horses maintained outdoors was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The proposed reasons for these contrasting results can only be hypothesised at this stage; however, they include the following: differences in sample collection time points in relation to either the time of challenge or the onset of clinical signs ; a unique equine pulmonary immunological response that fails to meet the current hypersensitivity subdivision definitions precisely; varied immunological mechanisms leading to a common disease phenotype or a mixed Th1/Th2 response . The latter 2 proposals may not be unexpected considering the fact that airborne organic dust, exposure to which constitutes the recognised method of disease induction and therefore subject categorisation into ‘susceptible’ and ‘nonsusceptible’, contains numerous proinflammatory agents (allergenic and nonallergenic), many of which probably have the ability to skew the ultimate cytokine and gene expression profile, dependent on their concentration relative to other dust components.…”
Section: Pathogenesismentioning
confidence: 99%
“…The proposed reasons for these contrasting results can only be hypothesised at this stage; however, they include the following: differences in sample collection time points in relation to either the time of challenge or the onset of clinical signs ; a unique equine pulmonary immunological response that fails to meet the current hypersensitivity subdivision definitions precisely; varied immunological mechanisms leading to a common disease phenotype or a mixed Th1/Th2 response . The latter 2 proposals may not be unexpected considering the fact that airborne organic dust, exposure to which constitutes the recognised method of disease induction and therefore subject categorisation into ‘susceptible’ and ‘nonsusceptible’, contains numerous proinflammatory agents (allergenic and nonallergenic), many of which probably have the ability to skew the ultimate cytokine and gene expression profile, dependent on their concentration relative to other dust components.…”
Section: Pathogenesismentioning
confidence: 99%
“…In previous studies in humans, CD44 positive cells in gastric cell lines were associated with increased chemoresistance and invasiveness [66]. Additionally, CD44 positive gastric tumors were associated with larger tumor size, a lower grade of differentiation, tumor relapse, lymph node invasion, distant metastasis and reduced survival [63][64][65][66]. It seems that CD44 may represent an important biomarker and a promising therapeutic target in canine gastric carcinomas.…”
Section: Discussionmentioning
confidence: 93%
“…CD44 serves as a signaling platform, with transmembrane and cytoplasmic domains as a co-receptor for various types of cell surface receptors that modulate cell adhesion, migration, proliferation, differentiation and survival [63][64][65][66]. In humans, its role in the adaptive plasticity and survival of cancer cells in processes like epithelial to mesenchymal transition, invasion and metastasis has been widely studied [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the study by Pietra et al, 2011, although a significant overexpression of IL-8 and TNFα mRNA on BALF was observed in the group of treated horses, with a peak around the ninth day, a comparison between exposed and unexposed horses does not reveal significant differences [ 64 ]. According to the authors, this evidence could depend on the loss of uniformity of the sample, since the evolution of the pathology represents a continuum from healthy to pathological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on horses with severe equine respiratory syndrome have revealed an increase in the gene expression of the pro-inflammatory cytokine IL-8 in bronchoalveolar cells [ 19 , 38 , 40 , 52 , 58 , 59 ], as well as an increase in IL-8 protein concentration in BALF [ 19 , 37 , 38 , 40 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%